Da casa para a escola, da escola para casa: uma análise jurídica da proposta do homeschooling à luz do princípio da solidariedade - Ferri, Felipe Eduardo Ramos de Oliveira (2023)
This research intends to analyze the conflict of interest between the modalities of school education and homeschooling, in face of the movement in support of homeschooling. The juridical perspective was chosen, considering that the theme has been a constant subject on the agenda of the three political wings of the republic. In this sense, the discussion about deschooling is conflated with the constitutionality concept, therefore the following question is posed: can school teaching be replaced exclusively by homeschooling? For such purpose, we made a historical exploration of the Brazilian school system, as well as the juridical and legal context. There was also the conceptualization of home schooling, the analysis of the Executive Branch with the emergence of the Ministry of Education (MEC) and the electoral politics, as well as the analysis in the Judiciary Branch of the decision of the Federal Supreme Court in RE 888.815/RS and the Legislative Branch's analysis of laws and bills. Lastly, the legal interpretation under the prism of the principle of solidarity was performed for the examination of the constitutionality of the educational modalities. This is both a bibliographical and document-based study, supported by articles, dissertations, theses, books, virtual journal articles, court decisions, and legislative documents. The unconstitutionality of the proposal for unschooling was confirmed due to the impossibility of removing the legitimacy of the Government in the provision of education, by means of school education. Furthermore, through the interpretation of the principle of solidarity, it is possible to draw an understanding of unconstitutionality in the face of complementary solidarity, but such principle also enables the reading of the constitutionality of exclusive home teaching in the light of coexisting solidarity.